”Kasama Weki” in the Architecture of the West Nusa Tenggara Weaving Museum - Nafasia, Sahadat; Anggita, Diptya (Institut Seni Indonesia Bali, 2024)
The aim of this research is to incorporate the wisdom of West Nusa Tenggara, Indonesia, into the design of the museum building, to preserve culture as a symbol of respect and love for the Indonesian homeland. The approach is carried out using a qualitative-correlational analysis approach to local socio-cultural activities and also using a conceptual design approach regarding design themes that highlight a cultural wisdom in Dompu called